Pengaruh Komunikasi Interpersonal Terhadap Kinerja Karyawan Pada Rumah Sakit Mulyasari Jakarta - Irawan, Pristanto Ria; Abdillah, Abdillah; Taryanto, Taryanto; Novita, Nevelyn Pitry (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The purpose of this study was to determine the effect of interpersonal communication on employee performance at Mulyasari Hospital, JakartaThis study uses a quantitative descriptive method with data collection techniques through distributing questionnaires, and library data. In this study, the sample used was 47 employees of Mulyasari Hospital, using a simple linear regression data analysis technique.The results of this study indicate that there is influence between variables interpersonal communication to variables employee performance At the Jakarta Mulyasari Hospital because the calculated t value of 7.091 is greater than the t table value of 2.012 so that H1 is accepted and the t calculated value lies in the area of rejection of H0 or H1 accepted. Then variables interpersonal communication have a positive influence strong r value of 0,726 (located in the correlation coefficient interval 0.60-0.799) and has a contribution of52,8% on the effective work variable, while the rest is equal to47,2% influenced by other factors. Furthermore, it can be known that the regression equation that can be used to predict that is Y’ =12,760 + 0,786X